Clonal evolution in myelodysplastic syndromes - da Silva-Coelho, Pedro; Kroeze, Leonie I; Yoshida, Kenichi; Koorenhof-Scheele, Theresia N; Knops, Ruth; van de Locht, Louis T; de Graaf, Aniek O; Massop, Marion; Sandmann, Sarah; Dugas, Martin; Stevens-Kroef, Marian J; Cermak, Jaroslav; et al. (Nature communications, 2017)
Cancer development is a dynamic process during which the successive accumulation of mutations results in cells with increasingly malignant characteristics. Here, we show the clonal evolution pattern in myelodysplastic syndrome (MDS) patients receiving supportive care, with or without lenalidomide (follow-up 2.5-11 years). Whole-exome and targeted deep sequencing at multiple time points during the disease course reveals that both linear and branched evolutionary patterns occur with and without disease-modifying treatment. The application of disease-modifying therapy may create an evolutionary bottleneck after which more complex MDS, but also unrelated clones of haematopoietic cells, may emerge. In addition, subclones that acquired an additional mutation associated with treatment resistance (TP53) or disease progression (NRAS, KRAS) may be detected months before clinical changes become apparent. Monitoring the genetic landscape during the disease may help to guide treatment decisions.
Keywords: Thalidomide; thalidomid; Membrane Proteins; inhibitory angiogeneze; regulace genové exprese u nádorů; Humans; Monitoring, Physiologic; lidé středního věku; Disease Progression; Biomarkers, Tumor; Tumor Suppressor Protein p53; nádorový supresorový protein p53; Female; mutace; Aged; management nemoci; klonální evoluce; senioři; lidé; chemorezistence; protoonkogenní proteiny p21(ras); sekvenování exomu; myelodysplastické syndromy; Exome Sequencing; nádorové biomarkery; monitorování fyziologických funkcí; Disease Management; Lenalidomide; Follow-Up Studies; ženské pohlaví; GTP-fosfohydrolasy; Male; Middle Aged; Proto-Oncogene Proteins p21(ras); Angiogenesis Inhibitors; membránové proteiny; Bone Marrow Cells; progrese nemoci; Myelodysplastic Syndromes; Mutation; mužské pohlaví; Gene Expression Regulation, Neoplastic; Clonal Evolution; lenalidomid; Drug Resistance, Neoplasm; následné studie; buňky kostní dřeně; GTP Phosphohydrolases